ANALYSIS OF STUDENTS' NUMERATION LITERACY LEVELS IN SOLVING HOTS QUESTIONS BASED ON ETHNOMATHEMATICS - Suryanti, Ristyana; Fadlil, Muhammad; Jahidin, Jaja; Utami, Sri (PT. BATARI EDU CALYA, 2023)
Three abilities are necessary for pupils to master in the twenty-first century: competency, literacy, and character quality. The development of pupils' thinking and reasoning skills—which are closely related—can be facilitated by numeracy literacy. The purpose of this study is to characterize students' proficiency in numeracy in answering higher-order thinking skill (HOTS) questions based on ethnomathematics. The purpose of the preparation of the questions is to assess students' comprehension of the material by giving priority to their numeracy and literacy abilities. The research subjects for this descriptive qualitative study are the seventh-grade pupils of AZ-Zikra Integrated Islamic Middle School for the 2023–2024 school year. Tests and interviews are the methods used in this study to gather data. With a percentage result of 55%, it was determined that students' numeracy literacy abilities were dominating at a low level. A total of 33 test-takers were picked from 6 students at different levels for interviews to support the study findings.